Prevalence of antenatal depressive symptoms among women in Sabah, Malaysia - Mohamad Yusuff, Aza; Tang, Li; Binns, Colin; Lee, Andy (2016)
OBJECTIVE: To investigate the prevalence of antenatal depression and to assess whether the common risk factors identified in previous studies were applicable to women in Sabah, Malaysia. METHODS: A prospective cohort study of 2072 women was conducted in Sabah during 2009-2010. Participants were recruited at 36-38 weeks of gestation to complete a self-administered questionnaire regarding their demographic, socioeconomic and health characteristics. The presence of depression was assessed using the validated Malay version of the Edinburgh Postnatal Depression Scale. RESULTS: The prevalence of antenatal depression was 13.8% [95% confidence interval (CI) 12.3%, 15.3%]. Women who were happy with the pregnancy [odds ratio (OR) 0.43, 95% CI 0.21, 0.89] and those with a planned pregnancy (OR 0.45, 95% CI 0.33, 0.60) were less likely to suffer from antenatal depression. Pregnant mothers who were taking oral contraceptives before pregnancy (OR 1.63, 95% CI 1.20, 2.22) and women who experienced antenatal anxiety (OR 3.17, 95% CI 2.35, 4.26) appeared to have an increased risk of antenatal depression. CONCLUSION: A substantial proportion of women suffered from antenatal depression in Sabah, Malaysia. Screening and culturally tailored intervention programs targeting vulnerable subgroups of women in the early stage of pregnancy are recommended to deal with the problem.